Germany's funding to the UNDS: Towards a better mix for stronger multilateralism - Silke Weinlich; Max-Otto Baumann; Erik Lundsgaarde (Deutsches Institut für Entwicklungspolitik (DIE), 2020)
Since 2016, Germany has been the second largest contributor to the United Nations development system (UNDS) for development-related and humanitarian activities, after the United States of America. The biggest increase in Germany's funding has been in the form of earmarked contributions, that is, funding with specified geographic and thematic purposes. While humanitarian funding to agencies such as the United Nations High Commissioner for Refugees (UNHCR), the World Food Programme (WFP) and the United Nations Children's Fund (UNICEF) accounts for the bulk of Germany's contributions to the United Nations (UN), development-related funding for the United Nations Development Programme (UNDP), the United Nations Population Fund (UNFPA) and UN Women also experienced a sharp rise. More recently, core contributions, which can be used by multilateral organisations with greater discretion, have also increased, most notably as part of the coronavirus (COVID-19) emergency response. The significant increase signals that Germany places trust in the UN, including in times of crisis, and deems it to be of real importance. It is now time for Germany to more explicitly recognise its strategic interest in a strong and effective UNDS that can reinforce its foreign policies regarding stabilisation, reconstruction, refugees and the climate. Through multilateral organisations states can achieve more than they can alone. Although earmarked funding has helped the UNDS to expand its scope and scale, in the most prominent forms it has many negative repercussions in terms of efficiency, effectiveness and legitimacy. Earmarking also comes with direct costs to German actors, who face challenges stemming from the multitude of earmarked funding arrangements and their administrative burden. In addition, the German government presents itself in a fragmented manner with regard to the UNDS, with differences across and within ministries and implementing agencies. For Germany, being in the prominent position of second largest contributor to the UNDS, at a time when the largest contributor is withdrawing funding, comes with responsibilities and opportunities. To be an effective supporter of multilateralism, the German government needs to get its own house in order. * It should view its allocation decisions as a means towards strengthening multilateralism and supporting UN reforms, and to that end it should work towards a better balanced funding mix with greater shares of flexible funds. * It should more clearly communicate and justify its increased engagement in the UNDS to the German public and increase the coherence of its multilateral efforts. * It should assess the hidden costs that arise through the use of implementing agencies and improve guidance on earmarked funding in line with commitments made in the context of the Grand Bargain (2016) and UN Funding Compact (2019). * It should stabilise the recently raised levels of core contributions to UN development agencies, recognise the strategic importance of core contributions and also make greater use of softly earmarked forms of funding.
Keywords: 330